Population genetics study of Strongyloides fuelleborni and phylogenetic considerations on primate-infecting species of Strongyloides based on their mitochondrial genome sequences. (February 2023) - Ko, Phoo Pwint; Haraguchi, Misaki; Hara, Takashi; Hieu, Duong Duc; Ito, Ayaka; Tanaka, Ryusei; Tanaka, Mio; Suzumura, Takafumi; Ueda, Miya; Yoshida, Ayako; Maruyama, Haruhiko; Nagayasu, Eiji
Abstract: Strongyloides is a genus of parasitic nematodes of vertebrates comprising approximately 50 documented species, each with various host ranges. Among these, three species ( S. stercoralis, S. fuelleborni, and S. cebus ) are known to infect primate hosts. S. fuelleborni typically infects non-human primates in the Old World. To complement the existing information on the global genetic structure of this species, we conducted a genotyping study of S. fuelleborni samples collected from rhesus macaques in Myanmar, Japanese macaques in Japan, and some zoo-kept primates. This study identified a novel haplotype group in isolates from the Myanmar rhesus macaques. Subsequently, we obtained the complete or nearly complete mitochondrial genome sequences of S. fuelleborni, S. cebus ( Strongyloides of New World monkeys), and S. vituli ( Strongyloides of cattle). Phylogenetic analysis based on concatenated mitochondrial protein sequences of various Strongyloides species indicated a close relationship between S. fuelleborni, S. vituli and S. papillosus ( Strongyloides in sheep and cattle). S. cebus is quite distantly related to both S. fuelleborni and S. stercoralis, which led to the hypothesis that the three primate Strongyloides species evolved independently as parasites of primates. Graphical abstract: Unlabelled Image